2017
DOI: 10.1186/s12575-017-0056-3
|View full text |Cite
|
Sign up to set email alerts
|

Cell Counting and Viability Assessment of 2D and 3D Cell Cultures: Expected Reliability of the Trypan Blue Assay

Abstract: BackgroundWhatever the target of an experiment in cell biology, cell counting and viability assessment are always computed. The Trypan Blue (TB) assay was proposed about a century ago and is still the most widely used method to perform cell viability analysis. Furthermore, the combined use of TB with a haemocytometer is also considered the standard approach to estimate cell population density. There are numerous research articles reporting the use of TB assays to compute cell number and viability of 2D and 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 49 publications
0
57
0
Order By: Relevance
“…The Trypan Blue Exclusion assay is notorious for low accuracy, poor reproducibility and high variation between counts of the same preparation of cells, thought to be caused by non-specific binding of the TB dye to cellular artifacts [54]. Our optimized TB assay has coefficients of variation similar to, or lower than those reported previously [54] [57] [58]. In the present study, when preparations containing 625 granulosa cells were counted on four separate occasions, the intra-assay CoV of 7.6%, and the inter-assay CoV was 4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Trypan Blue Exclusion assay is notorious for low accuracy, poor reproducibility and high variation between counts of the same preparation of cells, thought to be caused by non-specific binding of the TB dye to cellular artifacts [54]. Our optimized TB assay has coefficients of variation similar to, or lower than those reported previously [54] [57] [58]. In the present study, when preparations containing 625 granulosa cells were counted on four separate occasions, the intra-assay CoV of 7.6%, and the inter-assay CoV was 4%.…”
Section: Discussionmentioning
confidence: 99%
“…Piccinini F, Tesei A, Arienti C and Bevilacqua A [54] found no difference in viability when cells retrieved from two dimensional (2D) or three dimensional (3D) culture systems were assessed by TB. Cell viability and density measures varied by 5% and 20% respectively, with percent error in estimating cell numbers higher for 3D systems (21%) than for 2D systems (17%) [54]. Other studies reported coefficients of variation (CoV) for estimating cell numbers using TB from 4.5% [57] to 6.9% [58].…”
Section: Introductionmentioning
confidence: 99%
“…Using the appropriate dose for cell s' treatment is a very important issue, these doses should be chosen in a way that does not cause cell death and also have the maximum efficiency on cell differentiation (Piccinini et al, 2017). To determine the appropriate dose for the induction of differentiation, trypan blue assay was used; this assay detects the cell metabolic activity and viability (Piccinini et al, 2017). The results indicated that, the doses of fisetin that were less than 200 µg/ml had no significant effects on the proliferation of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…This method was done as demonstrated previously [42]. Briefly, cells were plated into 96 well plates (1×10 5…”
Section: Trypan Blue Dye Exclusion Assaymentioning
confidence: 99%